Satisfaction with life, work, and country, in staff of a Costa Rican university: comparison of headquarters and regional centers (UNED Research Journal, 2019)
Introduction: Satisfaction has been the subject of study by various disciplines, whose interest is to determine which factors or variables make their grade higher in an individual or in another if they have the same environmental and environmental conditions. The level of satisfaction is subjective and will depend to a great extent on the attitudes of the individual in relation to the extrinsic factors that surround him. Objective: To compare the level of satisfaction in the officials of the central headquarters and the university centers of a state university of Costa Rica. Methods: In the present study, we measured satisfaction in three dimensions: aspects of life, work and national scope, from which an index of personal satisfaction is calculated; the results obtained are compared between the University Center officials and the officials of the Headquarters of a state university of Costa Rica. Results: The level of satisfaction is higher in the capital, except for work, where there is no difference. Conclusions: The economic disadvantage in the regional centers matches a less optimistic view of the country and a lower level of personal satisfaction with life.
Keywords: well-being; lifestyle; quality of life; happiness; mental health; achievements